2018
DOI: 10.1016/j.scitotenv.2017.10.101
|View full text |Cite
|
Sign up to set email alerts
|

No increase in marine microplastic concentration over the last three decades – A case study from the Baltic Sea

Abstract: Microplastic is considered a potential threat to marine life as it is ingested by a wide variety of species. Most studies on microplastic ingestion are short-term investigations and little is currently known about how this potential threat has developed over the last decades where global plastic production has increased exponentially. Here we present the first long-term study on microplastic in the marine environment, covering three decades from 1987 to 2015, based on a unique sample set originally collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(86 citation statements)
references
References 62 publications
6
65
1
Order By: Relevance
“…Similar to the results presented here, Beer et al, (2017) found no trends in the abundance of microplastics ingested by pelagic fish from the Baltic sea over a 28 year dataset (1987 -2015), however the authors did not characterise polymer types preventing comparison with our findings. In fact, the current study appears to be the first long-term (decadal/multi-decadal) investigation to characterise microplastic polymers.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar to the results presented here, Beer et al, (2017) found no trends in the abundance of microplastics ingested by pelagic fish from the Baltic sea over a 28 year dataset (1987 -2015), however the authors did not characterise polymer types preventing comparison with our findings. In fact, the current study appears to be the first long-term (decadal/multi-decadal) investigation to characterise microplastic polymers.…”
Section: Discussionsupporting
confidence: 84%
“…With the continued and increasing input of plastic to the oceans (Geyer et al, 2017) it might be expected that surface concentrations would also increase over time, however data reveal inconsistencies. The North Pacific Subtropical Gyre has been documented to be accumulating plastics (Goldstein et al, 2012;Lebreton et al, 2018) while no such trends have been observed in other surface waters (Beer et al, 2017;Law et al, 2014Law et al, , 2010ter Halle et al, 2016). Global ocean budgeting identifies large discrepancies between expected and observed surface quantities (Cozar et al, 2014;Eriksen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Under OSPAR an example of a threshold value for assessing Good Environmental Status would be based on monitoring the quantity and incidence of litter ingested by Fulmarus glacialis , North Sea northern fulmars, where a quantitative level target of <10% of North Sea fulmars should have no more than 0.1 g of plastic in their stomach over a continuous period of at least 5 yr in all North Sea regions (OSPAR Commission 2008; European Commission 2013). Generally, the stomach contents of northern fulmars have proved to be a cost‐effective biomonitor and can provide timely information related to the effectiveness of mitigation efforts at reducing plastic pollution by assessing both increasing and decreasing trends (van Franeker et al 2011; Avery‐Gomm et al 2012; Trevail et al 2015; Beer et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For example, an increase in litter densities at sea floor has been reported from the Arctic deep-sea observatory HAUSGARTEN between 2002 and 2011 (Bergmann and Klages, 2012). On the other hand, studies of microplastics in the surface and the water column in the Baltic Sea (Beer et al, 2017) and at the surface in the North Atlantic subtropical gyre (Law et al, 2010) and East FIGURE 8 | (A) Sailing routes for fisheries (green lines), (B) sailing routes for other than fisheries: oil tankers (brown), chemicals/product tankers (red), bulk ship (orange), general cargo ship (blue), cooling/freezing (magenta), passenger (yellow), other activities (peach). Taken from the website havbase.no, period: August 2016.…”
Section: Discussionmentioning
confidence: 99%